PENGARUH PENERAPAN TEKNIK PEMBELAJARAN TRI FOKUS STEVE SNYDER TERHADAP PENINGKATAN KEMAMPUAN MEMBACA EFEKTIF - Rizka Maya Sari (Universitas Negeri Medan, 2014)
This study aimed to determine the effect of learning techniques Tri Focus Steve Snyder to improved reading skills effectively. The population in this research were 260 students of class X SMA Negeri 1 Talawi Coal District. The sample in this study amounted to 43 people were taken to probaliti techniques. The instruments used to collect the data is an essay test. The method used in this study is a quasi-experimental or quasi experiment. Of processing the data obtained with the pre test mean = 63.13, standard deviation = 7.23. The results of the post-test mean = 81.04, standard deviation = 7.43, then didapatlah t0 at 11.26. Furthermore t0 is known, then consulted with ttabel at 5% significance level with df = n-1 = 43-1 = 42. df = 42 obtained from the level of significance of 5% = 2.02. Because t0 obtained greater than ttable ie 19.88> 2.02, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Concluded that there is a significant influence on the use of learning techniques Tri Focus Steve Snyder to improved reading skills effectively 2nd semester class X SMA Negeri 1 Talawi District Coal learning year 2009/2010.Keywords : Learning Techniques Tri Focus Steve Snyder, Effective Reading